10-17 year-old`s 100m freestyle swimming speed, stroke pace and length profiling study - Karpov, V. Y.; Nekrasova, M. V.; Krasnov, R. B.; Garina, E. V. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to analyze the modern swimming speed control profiles in the youth 100m freestyle.